Study of the Acid Site Structure on the WO/ZrO Surface - V.V. Brei; O.V. Melezhyk; S.V. Prudius; G.M. Tel'biz; O.I. Oranska (Adsorption Science & Technology, 2005)
The IR and UV—vis diffuse reflectance spectra of mesoporous WO 3 /ZrO 2 are discussed and a scheme proposed for the acid site structure on the WO 3 /ZrO 2 surface. The high Brönsted acidity of WO 3 /ZrO 2 (H 0 ≤ −11.38) can be explained by the formation of large zirconium polytungstate species such as [≡ Zr 6 1/2+ W 6 6 +O 20 2− ] − H + on the WO 3 /ZrO 2 surface.